Persepsi Siswa Terhadap Pembelajaran Daring di SMA N 10 Batang Hari Jambi - Rosdilla, Rosi; Junaidi, Junaidi (Universitas Negeri Padang, 2022)
The purpose of this study is to analyze how students perceive online learning at SMA Negeri 10 Batanghari. This research is motivated by students' problems during online learning due to the covid-19 pandemic, from face-to-face learning to online learning using Whatsapp Group and Google Classroom media, besides that, students' responses are still low and their participation in online learning shows that students' readiness is still lacking. In this problem, the researcher describes how students perceive online learning at SMA Negeri 10 Batanghari. This research uses a qualitative approach with an intrinsic case study research type, the technique for selecting the selected informans was purposive sampling. The data collection techniques was done by means of observation, interview, and documentation study. Data wwere analyzed using techniques from Miles and Huberman consisting of data reduction, data presentation, and drawing conclusions. Informants in this study amounted to 28 people. This research was analyzed using the Construtivistic Theory by Jean Piaget. The result showed that threre were problem of online learning, such as difficult internet access, time limited, and the lesson difficult to understand because of that. The students said that there were so many problem of online learning in pandemic. So that, students perceive online learning at SMA Negeri 10 Batanghari is negative, because the lesson can’t optimal.